Investigating The Relationship between Land Surface Temperature (LST) and The Expansion of Built-up Land, A case Study of Baghdad, Iraq - Waleed, Noor; AL-Bakri , Maythm (Iraqi Journal of Science, 2023)
Converting green areas and agricultural land into built-up areas is one of the most significant effects of urbanization in Iraqi cities. Greenery spaces are a fundamental requirement for any city because they promote a healthy lifestyle and preserve urban areas' aesthetic and ecological beauty. The current study examines urbanization's effect on Baghdad city vegetation and land surface temperature. The Normalized Difference Built-Up Index (NDBI), Normalized Difference Vegetation Index (NDVI), Normalized Difference Water Index (NDWI), and Land Surface Temperature (LST) over Baghdad were used to determine the relationship among urban areas, vegetation areas, water bodies, and land temperature. The Baghdad-vector-data from the General Survey Authority was used along with Landsat Thematic Mapper for 2004 and 2008 and Landsat Operational Land Imager for 2013, 2017, and 2021. In order to understand the correlation between urban areas, water bodies, and green areas with LST, a correlation was carried out using ArcGIS software, and a scatter diagram was made to evaluate the relationship among the elements. The results showed that the temperature increased on Baghdad's land surface between 2004 and 2021. Moreover, built-up areas increased from 17% in 2004 to 53.2% in 2021; in contrast, the green areas drastically declined by 39.7%.